Nationalism, democracy, and development : state and politics in India - Bose, Sugata, 1956-; Jalal, Ayesha (Delhi ; New York : Oxford University Press, 1997)
Contributed essays.
Keywords: Nationalism -- India; Democracy -- India; India -- Politics and government -- 20th century